Classroom Management: How Important is Authentic Assessment of 21st Century Skills in Biology Education Students? - Anda Juanda (Postgraduate, University of Mataram, 2022)
To compete in the 21st century, educators need to equip students with various skills called 21st-century skills. The purpose of this research is to identify and describe the perceptions of biology education lecturers and students regarding the authentic assessment of 21st-century skills. The method used in this research is an internet-based survey method. The research participants consisted of 7 lecturers and 80 students majoring in biology education. The instrument used is a result questionnaire consisting of 11 questions for lecturers and ten questions for students. The survey results show that lecturers and students know about the components and urgency of 21st-century skills. In addition, the assessment of these skills is also quite often done. However, there are still some obstacles in authentically assessing 21st-century skills.